Discovery of a Giant Molecular Cloud at the Midpoint of the Galactic Bar Dust Lanes: M4.7–0.8 - Natalie O. Butterfield; Larry K. Morgan; Ashley T. Barnes; Adam Ginsburg; Savannah Gramze; Mark R. Morris; Mattia C. Sormani; Cara D. Battersby; Charlie Burton; Allison H. Costa; Elisabeth A. C. Mills; Jürgen Ott; et al. (The Astrophysical Journal, 2025)
We present the detection of a previously unknown giant molecular cloud (GMC) located at the midpoint of the Galactic Bar Dust Lanes (M4.7–0.8), using spectral line observations taken with the Green Bank Telescope. This  ∼60 pc long GMC is associated with accreting material that is transitioning from the quieter Galactic disk environment to the more extreme central molecular zone (CMZ) environment. Our 24 GHz single-dish radio observations targeted the NH _3 (1,1)−(4,4) and HC _5 N (9−8), known dense gas tracers. The observations reveal the main features of the GMC, which we have dubbed the “Nexus” and “Filament,” covering a 0 $\mathop{.}\limits^{\unicode{x000b0}}$ 5 × 0 $\mathop{.}\limits^{\unicode{x000b0}}$ 25 area at 31 ″ angular resolution. In this publication, we investigate the gas kinematics within the observed region and compare the distribution of molecular emission to previous infrared surveys to better understand the dust component. The observed gas tracers show centrally condensed cores corresponding to the positions of high dust column densities and low dust temperatures. We report the detection of a previously unknown NH _3 (3,3) maser, along with a 70 μ m source association, which supports the identification of this region as being actively star-forming. Gas emission in this region shows broad linewidths, comparable to values seen in CMZ clouds. The overall description of this cloud that we present is that of a highly dynamic region comprising dense gas and dust. This encapsulates a wide range of features associated with star formation, in addition to material transport related to the CMZ.